2004
DOI: 10.1023/b:johe.0000022026.20770.f4
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Use of Emergency Medical Resources Among Head Start Families: A Pilot Study

Abstract: The objective of this study was to determine whether self-care training with Head Start parents can improve their ability to manage the healthcare needs of their children measured by utilization of emergency department (ED) and physician services. Four hundred and six families in Head Start agencies were included in the study. Parents were given a low-literate self-help book entitled What To Do When Your Child Gets Sick. The study design included using multiple-choice, pre-and post-intervention survey data. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 3 publications
0
36
0
Order By: Relevance
“…Recently, a study of parents reported a 48% reduction in emergency department visits and a 37.5% reduction in clinic visits after 6 months of health training sessions and written materials in Head Start. 23 If interventions through child care can decrease emergency department visits and office visits, then they may prove to be cost-effective from a societal perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study of parents reported a 48% reduction in emergency department visits and a 37.5% reduction in clinic visits after 6 months of health training sessions and written materials in Head Start. 23 If interventions through child care can decrease emergency department visits and office visits, then they may prove to be cost-effective from a societal perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, EHS may be a potentially effective venue for URI educational interventions. [31][32][33] We conducted a randomized study of an educational intervention to increase health literacy regarding URI, with the goals of decreased PED visits and improved care practices among EHS families in a predominately Latino community.…”
Section: Discussionmentioning
confidence: 99%
“…In most instances, materials more appropriately matched with the reading skills of the intended audience have been associated with healthful outcomes, such as decreased emergency department visits (Herman & Mayer, 2004) and decreased anxiety (Coyne et al, 2003).…”
Section: Efficacious and Innovative Approachesmentioning
confidence: 99%